Biocompatible oligo-oxazoline crosslinkers: Towards advanced chitosans for controlled dug release - Lopes, Mafalda (2021)
Chitosan, a natural and abundant biopolymer has been long explored as a biocompatible material for the preparation of drug delivery devices. This strategy has been mostly accomplished using chemically crosslinked chitosan leading to more stable scaffolds. However, crosslinking has been shown to reduce both biocompatibility and swelling. In this work chitosan was crosslinked with novel biocompatible crosslinkers, based on oligo-oxazolines and glycidyl methacrylate copolymers, leading to patches with a very high swelling capacity. Dexamethasone therapeutics is strongly enhanced by a controlled release administration. This study shows that oligo-oxazoline-crosslinked chitosan is a suitable biomaterial for loading and controlled release of dexamethasone.